Improving Vocabulary Mastery by Using Snowball Throwing Technique - Yaqin, Muhammad Ainul; Fahruddin, Ahmad Hanif (Universitas Islam Lamongan, 2023)
This study aimed at improving vocabulary mastery by using snowball throwing technique to the seventh grade at SMPN 1 Karanggeneng in academic year 2014/2015. Considering that many find difficulties in vocabulary mastery. In this research, the writer focuses on using snowball throwing technique that can help students to improve their vocabulary mastery.The design of this research was Classroom Action Research (CAR). The subjects of this study were 21 studentsâ€™ of the seventth grade (class C) of SMPN 1 Karanggeneng in academic year 2017/2018. The result of this study showed that the score greater than or equal to 76 in Cycle I. Only 48% (10 students of the class) were able to reach the criteria of success, and 11 or about 52% students did not reach the criteria of success. It is different from the first cycle, the average score in Cycle 2 was fairly satisfying, the score was greaterÂ than or equal to 76, increasing into 76,19% (16 students of the class) were able to reach the criteria of success, and 5 or about 24% students who did not achieve the criteria of success. Based on the result of the students observations and post test, the studentsâ€™ improvement is significant. The implementation of snowball throwing technique obviously could help the students in vocabulary achievement. Finally, the writer suggests that the teacher should apply the snowball throwing techinque. Considering snowball throwing technique is technique to solve problem in vocabulary mastery. By using various technique in teaching English, especially in vocabulary mastery, it makes the students enjoy in learning it and automatically can improve their vocabulary mastery.